Parâmetros metabólicos e sua relação com mastite e resistência à insulina em vacas leiteiras - Schwegler, Elizabeth (2012)
The peripartum in dairy cows (three weeks before and three weeks after calving) is characterized by large changes in physiological demands in the animal where management practices, particularly nutrition, strongly influences the incidence of peripartum disorders and subsequent milk production. Most of the studies in that period in dairy cows are focused on confined systems where milk production is high. Therefore, the aim of this study was to assess metabolic markers associated with the occurrence of clinical and subclinical mastitis and insulin resistance in dairy cows in semi extensive system. Our study was divided into two major experiments with the following hypothesis: 1) medium milk production primiparous cows in semi extensive system have predictive metabolic markers of clinical and subclinical mastitis in the prepartum, 2) medium milk production pluriparous dairy cows with low rate of glucose metabolism during the prepartum, which is an indicative of insulin resistance, have higher minerals excretion in the postpartum period. In experiment 1, blood concentrations of NEFA in the prepartum period were higher, in contrast, phosphorus and glucose were lower (P <0.05) in animals with clinical mastitis postpartum. In experiment 2, pluriparous dairy cows with low rate of glucose metabolism in the prepartum had higher urinary calcium excretion in both prepartum and postpartum periods, and also the highest NEFA concentration in the prepartum period (P <0.05). The blood concentrations of calcium in dairy cows with high rate of glucose metabolism in the postpartum was elevated from the prepartum period and remained in the postpartum (P <0.05). Dairy cows kept in semi extensive system with moderate production level had predictive markers of mastitis in the prepartum, as previously demonstrated by other authors in more intensified systems of higher requirements for the animal. The highlighted marker was NEFA, however, in the second study it was shown in higher concentrations in the pluriparous dairy cows with low rate of glucose metabolism at prepartum, emphasizing the importance of this marker also in the insulin resistance.